The The Effects of Annual GDP growth on Consumption Spending: Evidence from West African Countries - Ismaila Y Jammeh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study examines the effect of annual growth in gross domestic product on consumption spending in the West African Countries from the period 2005 to 2020. Consumption has been a fundamental driver of economic growth, and the insufficient consumption spending will lure firms to lay off workers which can lead to short run fluctuation in the economy. The study employed a dynamic panel model with a set of estimation strategies such as fixed and random effect, Anderson and Hsiao (1982) estimation, difference and System-Generalized Methods of Moment and Least Square Dummy Variable estimation methods to correctly assess how annual GDP growth affect consumption spending in these countries including additional variables such as, Lag consumption spending, foreign direct investment, consumer prices as a measure of inflation and a vector of control such as capital formation and annual population growth. The study found that annual GDP growth and Foreign direct investment has a significant impact on increasing consumption spending thus annual GDP growth is the most crucial factor for increasing consumption spending in these countries. Moreover, lagged consumption spending is also found to have a negative significantly effect in reducing current consumption spending while gross capital formation and annual population growth are found to have an insignificant effect in reducing consumption spending in all the estimates except in the Anderson and Hsiao (1982) estimation method which shows a positive relationship with consumption spending.